Resective epilepsy surgery for West syndrome: The Hypsarrhythmic Asymmetric Scoring Scheme is a determining predictor of seizure outcome. (October 2022) - Li, Lin; Lin, Sufang; Tan, Zeshi; Chen, Li; Zeng, Qi; Sun, Yang; Li, Cong; Liu, Zhenzhen; Lin, Chun; Ren, Xiaofan; Zhang, Tian; Li, Ying; et al.
Highlights: Hypsarrhythmic asymmetric scoring scheme (HASS) was established to quantify the degree of hypsarrhythmic asymmetry. HASS score was proved to be a determining indicator of favorable postsurgical outcome. Receiver operating characteristic analysis showed that a threshold of 7 yielded a better seizure outcome with a sensitivity of 97.06% and specificity of 83.33%. Abstract: Objective: It has been suggested that asymmetric hypsarrhythmia is associated with structural etiology. We devised the Hypsarrhythmic Asymmetric Scoring Scheme (HASS) to quantify the degree of hypsarrhythmic asymmetry in a retrospective series of patients who underwent surgical treatment at our center. The present study aimed to investigate the role of HASS in predicting the postsurgical seizure outcomes. Methods: We retrospectively analyzed the records of 46 children with hypsarrhythmia who underwent resective epilepsy surgery between 2018 and 2020 and were followed up for at least 1 year after surgery. Hypsarrhythmia severity in each hemisphere was quantified and scored. The HASS score was calculated as the difference between the two hemispheres. Univariate results were submitted to logistic regression models to identify independent predictors for favorable surgical outcomes. Results: Of the 46 patients who underwent resective surgery, Engel's class I–Ⅱ outcomes were achieved in 34 (73.9%). The Engel I–Ⅱ group had a significantly higher HASS score than the Engel Ⅲ–Ⅳ group ( p <0.001). Multivariate analysis showed that the HASS score was the only significant predictor of good outcomes ( p  = 0.011). Further receiver operating characteristic analysis showed that a threshold of 7 yielded a better seizure outcome with a sensitivity of 97.06% and specificity of 83.33%. Significance: As the first hypsarrhythmia scoring system specially designed for presurgical evaluation, the HASS score may contribute to predicting the postsurgical seizure outcome from the electroencephalography perspective.